Bioactive glasses promote rapid pre-osteoblastic cell migration in contrast to hydroxyapatite, while carbonated apatite shows migration inhibiting properties - Kajander Karoliina; Sirkiä Saara V.; Vallittu Pekka K.; Heino Terhi J.; Määttä Jorma A. (Nature Research, 2025)
Different biomaterials have been clinically used as bone filling materials, although the mechanisms behind the biological effects are incompletely understood. To address this, we compared the effects of five different biomaterials: two bioactive glasses (45S5 and S53P4), hydroxyapatite (HAP), carbonated apatite (CAP), and alumina on the in vitro migration and viability of pre-osteoblastic cells. In addition, we studied the effects of biomaterials’ calcium release on cell migration, viability and differentiation. We found differences between the materials as the bioactive glasses promoted rapid pre-osteoblastic cell migration. In contrast, CAP decreased cell migration, which was also associated with lower activity of migration related kinases. Bioactive glasses released significant amounts of calcium into the media, while CAP decreased the calcium concentration. The response of cells to calcium was mechanistically studied by blocking calcium sensing receptor (CaSR) and ATP-gated ion channel P2X7, but this had no effect on cell migration. Surprisingly, HAP and CAP initially decreased cell viability. In summary, bioactive glasses 45S5 and S53P4 had significant and long-lasting effects on the pre-osteoblastic cell migration, which could be related to the observed calcium dissolution. Additionally, bioactive glasses had no negative effects on cell viability, which was observed with HAP and CAP.